Whole Exome Analysis to Select Targeted Therapies for Patients with Metastatic Breast Cancer – A Feasibility Study - Jaeger, Bernadette Anna Sophia; Krawczyk, Natalia; Japp, Anna Sophia; Honisch, Ellen; Köhrer, Karl; Scheuring, Sibylle; Petzsch, Patrick; Neubauer, Hans; Volkmer, Anne Kathrin; Esposito, Irene; Ruckhäberle, Eugen; Niederacher, Dieter; Fehm, Tanja (Geburtshilfe und Frauenheilkunde, 2023)
The purpose of this feasibility study was to select targeted therapies according to “ESMO Scale for Clinical Actionability of molecular Targets (ESCAT)”. Data interpretation was further supported by a browser-based Treatment Decision Support platform (MH Guide, Molecular Health, Heidelberg, Germany).We applied next generation sequencing based whole exome sequencing of tumor tissue and peripheral blood of patients with metastatic breast cancer (n = 44) to detect somatic as well as germline mutations.In 32 metastatic breast cancer patients, data interpretation was feasible. We identified 25 genomic alterations with ESCAT Level of Evidence I or II in 18/32 metastatic breast cancer patients, which were available for evaluation: three copy number gains in HER2, two gBRCA1, two gBRCA2, six PIK3CA, one ESR1, three PTEN, one AKT1 and two HER2 mutations. In addition, five samples displayed Microsatellite instability high-H.Resulting treatment options were discussed in a tumor board and could be recommended in a small but relevant proportion of patients with metastatic breast cancer (7/18). Thus, this study is a valuable preliminary work for the establishment of a molecular tumor board within the German initiative “Center for Personalized Medicine” which aims to shorten time for analyses and optimize selection of targeted therapies.
Keywords: Mammakarzinom; zielgerichtete Therapie; Ganz-Exom-Sequenzierung; Entscheidungsplattform